Histone deacetylase (HDAC) 1 and 2 expression and chemotherapy in gastric cancer - Mutze, Kathrin Isabelle Amelie; Langer, Rupert; Becker, Karen; Ott, Katja; Novotny, Alexander; Luber, Birgit; Hapfelmeier, Alexander; Göttlicher, Martin; Höfler, Heinz; Keller, Gisela (Annals of surgical oncology, 2010)
Histone deacetylases (HDACs) modulate chromatin and may influence the effect of DNA-damaging drugs. We investigated HDAC1 and -2 expression in gastric carcinomas (GCs) for an association of patient outcome with conventional neoadjuvant chemotherapy. In vitro, HDAC inhibitors were evaluated as alternative treatment options.
Gesehen am 17.05.2023